Enzyme-Linked Immunosorbent Assay for Detection of Ochratoxin A - Pestka, J. J. (1981)
A simple microtest plate enzyme-linked immunosorbent assay was developed for the detection of ochratoxin A at levels as low as 25 pg per assay. The relative cross-reactivities of the antibody in this system with ochratoxin A (OA), OB, OC, and Oα were found to be 1.0, 0.14, 0.44, and 0.01, respectively.